GEOGRAPHICAL FIELD TRIPS DURING UNIVERSITY STUDIES. WHERETO? (II) - OANA-RAMONA ILOVAN; MARIA ELIZA DULAMĂ; KINGA XÉNIA HAVADI-NAGY; CRISTIAN NICOLAE BOŢAN; VIOREL GLIGOR; LILIANA CIASCAI; EMANUEL- CRISTIAN ADORE (Romanian Review of Geographical Education, 2019)
This paper analyses information and university students’s opinions, from the Faculty of Geography of Babeş-Bolyai University, Cluj-Napoca, Romania, regarding the field trips organised during their studies. Information and opinions were collected by means of a questionnaire administered in 2017. There were analysed: the number of field trips students participated at, their duration, sources of funding, types of learning activities and their efficiency, the places where the activities were organised, strengths and opportunities, weaknesses and threats, as well as improvement measures. The compulsory field trips are included and credited in the curriculum and completed with grades at all Bachelor specialisations. In addition, the professors organise short, optional thematic field trips in and around Cluj-Napoca. The results of the research revealed the professors’ expertise in organising field trips, such as duration, places studied, content proposed for learning, didactic and research methodology, devices and tools used. Results showed students’ greater involvement into compulsory field trips, compared to their participation at optional and short field trips organised in the local horizon. These results also highlighted the students’ desire to benefit of a better field trip activity offer and of a broad range of student-centered learning activities: discussions and debates, problem solving and exercises, individual and group investigations, and so on. Our research will be useful for professors who organise field trips with Geography students.